Comparison of Total Protein Levels in Lipemic Serum with Alpha Cyclodextrin, Gamma Cyclodextrin, and High-Speed Centrifugation Treatment - Tania, Aulia Rachma; Haryanto, Edy; Puspitasari, Ayu (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Lipemic serum can interfere with examination parameters that require light transmission and may lead to inaccurate analysis results. One of the tests carried out in the clinical laboratory is total protein. Handling of lipemic serum can be done by several methods including centrifugation and precipitation. Precipitation is carried out with cyclodextrins which are water soluble and can form complexes with water molecules, and are effective in overcoming disturbances of lipid particles in lipemic serum. This study aimed to compare and analyze total protein levels in lipemic serum treated with alpha cyclodextrin, gamma cyclodextrin, and high-speed centrifugation. This study was conducted at Surabaya Jemursari Islamic Hospital Laboratory in October 2021-May 2022 and aimed to analyze the difference in total protein levels in lipemic serum that has been treated with 20% alpha cyclodextrin, 20% gamma cyclodextrin, and with high-speed centrifugation treatment. The method used in this study was a pretest-posttest design, involving 9 lipemic serums in total that were visually visible. Determination of this study was performed by statistical analysis using the SPSS application. The asymptotic value obtained was 0.248 for alpha cyclodextrin treatment; 0,125 for gamma cyclodextrin treatment; and 0,229 for high-speed centrifuge treatment. Since the obtained asymptotic value was >0.05. It can be concluded that there was no significant differences in the treatment of lipemic serum with the treatment of alpha cyclodextrin, gamma cyclodextrin, and high-speed centrifugation.Keywords: cyclodextrin; high-speed; centrifugation; lipemic serum; total protein; precipitation